The Epidemiology of Sports and Recreation Related Toe Fractures in the United States - Dogerno Norceide BS; Gabriel I. Onor MD; Oluwatomi Akingbola MD; William Justice MD; Nana F. Amponsah BS; Abimbola Okulaja MD; Ifeanyichukwu Onor PharmD; Michael Okoronkwo MD; Chibuikem Nwizu BS; David Pedowitz MD (Foot & Ankle Orthopaedics)
Background: Fractures of the toes are among the most frequently diagnosed lower extremity fractures. In sports, toe fractures may present after diverse mechanisms of injury, varying severity, and varying implications for management. This study aimed to discern trends in toe fractures presenting to US emergency departments (EDs) particularly in association with sports and recreational activities. An additional aim of the study was to identify if rates of toe fracture presentation significantly decreased during the year 2020 at the height of the COVID-19 pandemic. Methods: We queried the National Electronic Injury Surveillance System (NEISS) database to identify toe fractures presented to US EDs from 2013 to 2022. The data outputs were analyzed by age group, sex, sport/recreational activity, and year. US Census data were used for calculation of incidence rates (IR) in 100,000 person-years. χ 2 tests and regression analyses were performed to determine significance. Grubbs’s test was performed to determine significant yearly outliers with particular attention to the year 2020. Results: A total of 921,033 toe fractures were identified across US EDs, with 175,864 cases associated with sports and recreation. Exercise (IR = 140.3) had the leading IR among sports/recreation followed by cycling (IR = 136.8), basketball (IR = 136.8), and football (IR = 94.9). Males accounted for 40.8% of fractures (IR = 23.0), whereas females contributed 59.2% (IR = 32.8). Toe fractures peaked in the 10- to 14-year-old age group in both males and females. Sports- and recreation-related toe fractures did not significantly decrease from 2013 to 2022, although all-cause toe fractures did significantly decrease as shown by a P value of .0037 from linear regression analysis of yearly trend in all toe fractures. The year 2020 was a significant outlier with a decrease in sports-related toe fractures though there was no significant decrease in all-cause toe fractures in 2020. Conclusion: Sports- and recreation-related toe fractures did not significantly decrease from 2013 to 2022, although a significant decrease in all-cause toe fractures was observed. Toe fractures continue to peak in the pediatric age groups, particularly 10-14 year-olds. Youth sports and recreation officials should be aware of the risks of toe fractures to aid in prevention. Level of Evidence: Level III, epidemiologic database, retrospective cohort studies.